DNA topoisomerase II is involved in regulation of cyst wall protein genes and differentiation in Giardia lamblia. - Bo-Chi Lin; Li-Hsin Su; Shih-Che Weng; Yu-Jiao Pan; Nei-Li Chan; Tsai-Kun Li; Hsin-Chih Wang; Chin-Hung Sun (Public Library of Science (PLoS), 2013)
The protozoan Giardia lamblia differentiates into infectious cysts within the human intestinal tract for disease transmission. Expression of the cyst wall protein (cwp) genes increases with similar kinetics during encystation. However, little is known how their gene regulation shares common mechanisms. DNA topoisomerases maintain normal topology of genomic DNA. They are necessary for cell proliferation and tissue development as they are involved in transcription, DNA replication, and chromosome condensation. A putative topoisomerase II (topo II) gene has been identified in the G. lamblia genome. We asked whether Topo II could regulate Giardia encystation. We found that Topo II was present in cell nuclei and its gene was up-regulated during encystation. Topo II has typical ATPase and DNA cleavage activity of type II topoisomerases. Mutation analysis revealed that the catalytic important Tyr residue and cleavage domain are important for Topo II function. We used etoposide-mediated topoisomerase immunoprecipitation assays to confirm the binding of Topo II to the cwp promoters in vivo. Interestingly, Topo II overexpression increased the levels of cwp gene expression and cyst formation. Microarray analysis identified up-regulation of cwp and specific vsp genes by Topo II. We also found that the type II topoisomerase inhibitor etoposide has growth inhibition effect on Giardia. Addition of etoposide significantly decreased the levels of cwp gene expression and cyst formation. Our results suggest that Topo II has been functionally conserved during evolution and that Topo II plays important roles in induction of the cwp genes, which is key to Giardia differentiation into cysts.